(untitled) (قضايا سياسية, 2024)
Transcendentalism believes in the power of the spirit and generosity of man and believes that he possesses the intrinsic capabilities that qualify him to build a society in which justice and freedom prevail and whose rights are not undermined or violated. Transcendental thought was revived by the philosopher Kant in the era of European Enlightenment, but it did not achieve a realistic impact on Western political thought. As for the intellectual and political climate The American was ready to adopt his ideas and apply them as part of building a civil-political society that coincided with the independence movement of 1776, and his intellectual influences turned into a common language between the state’s political elites and the general public, We find that the political and economic changes in the nineteenth and twentieth centuries did not give Transcendentalism and its ideas the opportunity to occupy the forefront at the level of contemporary American political thought, but its intellectual foundations were able to be deeply rooted in the thought and behavior of the individual and collective mind, which was embodied in the emergence of intellectual and political theories and theses with a purely American identity, and contributed Also by achieving the sustainability process to protect the values and principles of liberal democracy and later transforming it into a global model at the level of thought and political action.